LITERATURE REVIEW ON GLUCOSAMINE AND CHONDROITIN IN OSTEOARTHRITIS TREATMENT - Dang Thi Soa*, Vu Thi Thuy, Nguyen Duc Trung, Bien Thi Thuc Uyen, Le Thi Hai Yen, Tran Trung Hieu, Tran Thao Linh (Tạp chí Khoa học)
Osteoarthritis is a chronic disease primarily characterized by articular cartilage damage. In Vietnam, osteoarthritis accounts for a high percentage of musculoskeletal conditions, especially affecting the knee joints. Recently, slow-acting anti- osteoarthritis drugs, including glucosamine, chondroitin sulfate, and diacerein, have been suggested as key pharmacological options for treating this condition. However, Vietnamese-language resources on these active ingredients remain limited. This article provides a literature review on the efficacy and safety of these drugs to enhance their effective use in clinical practice. Results indicate that glucosamine and chondroitin are both effective and safe for osteoarthritis treatment, as demonstrated by the data analyzed in this study.